INTUISI SISWA MADRASAH IBTIDAIYAH (MI) DALAM PEMECAHAN MASALAH MATEMATIKA DIVERGEN - Abidin, Zainal (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
Intuition is an immediate cognition received directly (self evident), without a reasoning process in depth, without requiring a jastifikasi or mathematical proof. Intuition plays a role in understanding the mathematical statements. However, intuition is also very involved in solving mathematical problems. Philosopher and educational experts regard intuition as a mental strategy or method that allows one stating the essence / essence of a phenomenon. The purposed of this study were (1) describe the intuition of students in mathematical problem solving divergent. From the results of this study can be summarized as follows: a) in understanding the problem, the kind of intuition that can be used for students classified in this type of intuition affirmatory. b) in planning the solution, intuition is used for students is to try to use division and multiplication. Jenis intuition is classified in this type of anticipatory intuition c) in implementing the solution, intuition is used is by way of trial and error, students tried to halve the amount of money available, and then used to buy a mango half and half to buy guava. Students also use a way of trying to multiply the number of mangoes that will be purchased at the price of one mango fruit and the remainder is used to buy guava and vice versa. Thus the kind of intuition that is used in this type of student is classified as anticipatory intuition d) Looking Back, intuition is used is to add the price of one mango and guava fruit multiplied by the number of mango and guava are purchased. With this type of intuition is used for students classified in this type of intuition affirmatory.Keywords: Intuition, Pemecahan Masalah, Divergen